Review of Childhood in Ancient Egypt - Garroway, Kristine Henriksen (JAOS, 2024)
Childhood in Ancient Egypt. By Amandine Marshall. Translated by Colin Clement. Cairo: The American University in Cairo Press, 2022. Pp. xxxi + 266, illus. $70.